The frugal innovator creating change on a shoestring budget - Leadbeater, Charles (Palgrave Macmillan, 2014)
"Frugal innovation is a powerful new model for creating solutions for a world struggling with rapid population growth, exploding demand from consumers on modest incomes, and global pressure to minimize environmental damage. This new wave of innovation started in the developing world but is spreading globally. This inspiring book provides an insight into what promises to become a worldwide movement as large companies in developed economies start to learn from entrepreneurs in the developing world, who are coming up with radical solutions to pressing challenges. Frugal innovators follow four design principles to create these solutions: 'lean, simple, clean and social'. Frugal innovators are devising these new solutions for clean water and energy, affordable housing and health care, because the constraints they work give them no option but to think radically and challenge conventional wisdom. By unpicking the principles, drivers and methods for frugal innovation, Leadbeater's analysis and case studies lead to practical 'how-to' strategies for applying frugal innovation wherever you work. "-- Provided by publisher.